A Human Intestinal Infection Caused by a Novel Non-O1/O139 Vibrio cholerae Genotype and Its Dissemination Along the River - Fu, Songzhe; Hao, Jingwei; Jin, Shibo; Wu, Kui; Wang, Yi; Ye, Shigen; Liu, Ying; Li, Ruijun (Frontiers in Public Health, 2019)
Non-O1/O139 Vibrio cholerae is increasingly reported in the clinical settings. However, intestinal infections via the consumption of non-O1/O139 V. cholerae -carrying seafood are rarely documented in China. In this study, we reported a case of mild watery diarrhea in a young male, caused by non-O1/O139 V. cholerae in the downstream of Liaohe River. Epidemiological investigation showed that this intestinal infection potentially associated with the raw consumption of mollusc. Prior to this finding, we conducted a six-month pathogen surveillance of three locations along the Liaohe River and identified three environmental non-O1/O139 V. cholerae strains. To confirm the epidemiological links between clinical and environmental strains, high-resolution genomic typing was employed and revealed that V. cholerae isolated from human stool sample was genomically related to the one found in local mollusc and shared a common ancestor with other environmental strains obtained in the upstream sites of the Liaohe River. This fact suggests that the river is a nature reservoir for non-O1/O139 V. cholerae which poses a potential threat to the public health. In summary, our results support the hypothesis that the movement of the river can serve as a disseminator for the transmission of non-O1/O139 V. cholerae and deepen our insight on the transmission of non-pandemic V. cholerae strains.